Mini-Review on the Enzymatic Lipophilization of Phenolics Present in Plant Extracts with the Special Emphasis on Anthocyanins - Karina Jasińska; Agata Fabiszewska; Ewa Białecka-Florjańczyk; Bartłomiej Zieniuk (Antioxidants, 2022)
Different plant extracts have the potential to be important sources of phenolic compounds. Their antibacterial, antifungal and antioxidant properties are of interest to researchers due to various possibilities for use in the pharmacy, cosmetic and food industries. Unfortunately, the direct application of phenolics in food is limited because of their hydrophilic nature and low solubility. The review is devoted to the recent advances in the methods of lipophilization of phenolic extracts along with the use of enzymes. The concept of extract modification instead of single compound modification is based on the expected synergistic effect of many phenolic compounds. The main focus is on the phenolic compounds found in fruits, flowers and leaves of different common and underutilized as well as medicinal, folk-medicinal or endemic plants. The compiled papers point to the great interest in the modification of anthocyanins, highly active but often unstable phenolics. Some examples of other flavonoids are also outlined. The possible applications of the lipophilized plant extracts are presented for improving the stability of edible oils, decreasing the content of acrylamide, exhibiting higher color stability in thermal processing and increasing the nutritional value.